2016
DOI: 10.1155/2016/5976862
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cracking Analysis during Pipe Cooling of Mass Concrete Using Particle Flow Code

Abstract: Pipe cooling systems are among the potentially effective measures to control the temperature of mass concrete. However, if not properly controlled, thermal cracking in concrete, especially near water pipes, might occur, as experienced in many mass concrete structures. In this paper, a new numerical approach to simulate thermal cracking based on particle flow code is used to shed more light onto the process of thermal crack propagation and the effect of thermal cracks on thermal fields. Key details of the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The 2D particle flow was used to model a concrete slab that has a length of 1 meter and width of 0.5 m. The study concluded that thermal cracks might occur if the temperature of the cooling water is too low or the temperature gradient between the concrete and the cooling pipes is high. Bond breakages was observed where thermal cracks occurred [17].…”
Section: Post-cooling Of Concretementioning
confidence: 99%
“…The 2D particle flow was used to model a concrete slab that has a length of 1 meter and width of 0.5 m. The study concluded that thermal cracks might occur if the temperature of the cooling water is too low or the temperature gradient between the concrete and the cooling pipes is high. Bond breakages was observed where thermal cracks occurred [17].…”
Section: Post-cooling Of Concretementioning
confidence: 99%
“…ere is a large error between the temperature field of the dam reconstructed by the temperature extrapolation method and the actual temperature field of the dam. e other is using the numerical simulation method to establish the temperature field of the in-service concrete arch dam [15][16][17][18][19][20]. e temperature field of the concrete arch dam changes with the surrounding environment due to the actions of convection, radiation, and evaporative cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, the equivalent approach cannot describe the sharp temperature gradient around the cooling pipe and the temperature rise of water flow along the pipeline. While, many engineering examples show that a sharp cooling may produce a large global temperature gradient and tensile stress, which may lead to the generation and expansion of cracks from inside [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%